OPTIMIZATION OF THE NICKEL LOAD TEST PROCESS BEFORE LOADING IN THE MV. LUMOSOS STRIPE - M Adil Wanadi; Femmy Sofie Schouten; Wisnu Handoko; William Seno; Yus Rizal; Guntur Tri Indra (Meteor STIP Marunda, 2025)
Nickel Ore cargo is a cargo that requires special handling starting from checking before being loaded onto the ship and still on the barge, during the loading process, to its maintenance in the hatch during the ship's voyage. For this reason, attention is needed so as not to pose a danger to shipping safety. This study aims to find out things that can still be improved in the handling of nickel cargo in MV. Lumoso Raya so that important recommendations were obtained for ship safety. The research methods used are qualitative through direct observation in the field, interviews with related parties, literature studies, and documentation. The data obtained is then analyzed and presented in the form of a descriptive narrative. The results of the study show that there are still obstacles in handling nickel cargo before the loading process, namely the lack of understanding of the crew, and differences of opinion between the Officer On Watch or the guard officer and the shipper. The researcher proposed that familiarization is still needed to improve the knowledge of the crew, as well as an explanation of the Lumoso Circular no. 5/10/2017 owned by the company PT. Lumoso Pratama Line which is a guide for operational procedures on ships in loading nickel so that the process of loading nickel becomes more optimal and also guarantees the safety of ships in sailing